1993
DOI: 10.1007/bf01658714
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of factors influencing the prognosis of Japanese, German, and Dutch gastric cancer patients

Abstract: As a result of Japanese reports of improved survival of gastric cancer patients after extended lymph node dissection, a study was undertaken to evaluate factors that might influence these results. The influence of staging was evaluated by stratifying 1085 patients of the National Cancer Center of Japan and grouping them according to the three commonly used systems; UICC's old and new TNM systems (fourth edition) and the system of the Japanese Research Society for the study of Gastric Cancer (JRSGC). No surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(50 citation statements)
references
References 21 publications
2
48
0
Order By: Relevance
“…Koreans had a remarkably low proportion of cardia gastric cancer, contributing further to their overall advantage. Asian race has been shown to be an independent prognostic factor for gastric cancer survival in many studies [6][7][8][9][10][11][12][13][14][15][16][17]. Here, we bolster those findings, demonstrating with multivariate analyses that each of the six major Asian ethnic groups has a survival advantage compared to NHWs.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Koreans had a remarkably low proportion of cardia gastric cancer, contributing further to their overall advantage. Asian race has been shown to be an independent prognostic factor for gastric cancer survival in many studies [6][7][8][9][10][11][12][13][14][15][16][17]. Here, we bolster those findings, demonstrating with multivariate analyses that each of the six major Asian ethnic groups has a survival advantage compared to NHWs.…”
Section: Discussionsupporting
confidence: 52%
“…Compared to non-Hispanic whites (NHWs), Asian Americans, as a whole, have higher gastric cancer incidence, but also have better survival outcomes [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Previous research, while not conclusive, has linked the survival advantage of Asian Americans to tumors at a more distal anatomic site, diagnosis at earlier tumor stages, diagnosis at younger ages, and more aggressive treatment approaches [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 Although Hispanic ethnicity did not influence survival in the latter study, Asian race remained a favorable predictor of outcome. Stage migration, [8][9][10][11] treatment differences, [12][13][14] and differences in disease behavior [15][16][17][18][19] have been proposed to explain the differences in outcomes between Japanese patients and Western patients.…”
mentioning
confidence: 99%
“…To date, there has been no high-quality study that has reported biological differences in gastric cancer between Western and Japanese patients. Moreover, some studies report the similarity of gastric cancers in Western and Japanese patients [16,17]. Stage migration, due to more accurate nodal staging in Japan, can explain some part of the large differences in OS and RFS [18].…”
Section: Comparison Of Western and Japanese Trialsmentioning
confidence: 99%